Cost-Effectiveness of Oseltamivir and Favipiravir in Covid-19 Patients: a Cost-Effectiveness Analysis Study in a Hospital - Yusransyah Yusransyah; Baha Udin S.farm (JSFK (Jurnal Sains Farmasi & Klinis), 2025)
The COVID-19 pandemic poses not only a threat to health but also to the global economy, including healthcare costs. Although there is no specific drug for COVID-19 patients, there are antiviral drugs such as oseltamivir and favipiravir that can be used to treat COVID-19. The purpose of this study was to determine the most cost-effective antiviral therapy between oseltamivir and favipiravir for COVID-19 patients in one of the hospitals in Banten province. The pharmacoeconomic method used in this study was cost-effectiveness analysis by calculating the Average Cost-Effectiveness Ratio (ACER) and Incremental Cost-Effectiveness Ratio (ICER). The results of this study showed that the ACER value of the favipiravir group (IDR  364,010 (n = 7)) was lower than the oseltamivir group (IDR 431,744 (n = 7)), with an ICER value of IDR  60,605. Based on the results of the Mann-Whitney test, there was no significant difference between the costs of the favipiravir and oseltamivir groups (p value 0.940). The sensitivity test showed that the cost of medical consumables was the cost that had the greatest impact on cost-effectiveness. Based on the calculation results, it can be concluded that the favipiravir group is more cost-effective than the oseltamivir group.